Challenges Facing Street Vendors in Durban and the Role of The Law: A Means to Empowering Women - Noluthando Perceviarance Ndaba; Karunanidhi Reddy (African Journal of Inter-Multidisciplinary Studies)
As a vulnerable group in South Africa, women have been the primary victims of unemployment, the lack of access to income generation opportunities and barriers to sustainable livelihoods in general. Street vendors are a significant part of the economy, and their income supports several families and sustains their livelihoods. However, such vendors, particularly women, are faced with severe problems that interfere with their daily operations, as well as challenges relating to the law. Their low literacy levels mean they have an inadequate understanding of the laws and by-laws that regulate street vending. Even though the South African Constitution guarantees equal rights and protection, as well as the freedom to choose one's own occupation, trade or profession, street vendors, especially female vendors, are not adequately protected. The purpose of this study was to investigate the challenges faced by street vendors in the Durban area and to examine the role of the law in contributing to such challenges, as well as addressing them. Through a quantitative study using a survey, data was collected from street vendors in Durban. The study’s findings indicate that vendors lacked knowledge of their rights and faced poor working conditions, harassment by the police, evictions, impounding of goods and a lack of access to permits.